Influencia De Un Programa De Ejercicios Para El Desarrollo De La Coordinación Dinámica General En Nadadores De 9 A 12 Años (2015)
Coordinative work in swimming plays a very important role due to that it is a purely coordinated sport, which requires fluid, engage and harmonic movements. In this research, a number of key exercises are provided to coaches and swimmers to develop the coordinative capacity, which is not only important, but essential when practicing this Sport. Once coordinative difficulties was identified at the starting-point of teaching-learning process of Chest stroke style and Butterfly stroke style, in the Swim Team at the Asociación Club Campestre Armenia; Was given the task of determine the benefit to be derived by applying an exercise program for the development of the general dynamic coordination swimmers between the ages of 9-12 years old. For this test a cross-quantitative methodology quasi-experimental was used, with an Experimental group and a Control group, thus giving way to the realization of a series of pre-test of the general dynamic coordination, which found a lack of Coordinative Capacity swimmers; For this reason the adaptation of an existing exercise program and its implementation according to the context. Then the post-test was performed to observe the results. Finally a statistical analysis with the freeware program STATGRAPHICS, which yields a significant difference in outcomes between the Experimental group and the Control group.